2003
DOI: 10.1029/2001jb000609
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transform mapping of effective elastic thickness and plate loading: Validation using synthetic data and application to the study of southern African tectonics

Abstract: [1] We present a new wavelet transform method to map spatial variations in effective elastic thickness T e and plate loading ratio f. The method assumes a model of thin plate flexural isostasy to describe the mechanical response of the lithosphere to vertical loading. In this model, the rheological properties of the lithosphere are aggregated into the effective elastic thickness T e of an equivalent thin plate overlying an inviscid fluid. A number of methods have been developed to map spatial variations in T e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 50 publications
1
86
0
Order By: Relevance
“…[36] The preprocessing technique of mirroring the gravity/topography data before performing a Fourier transform has been performed in many studies [e.g., Zuber et al, 1989;Lowry and Smith, 1994;Macario et al, 1995;Hartley et al, 1996;McKenzie and Fairhead, 1997;Poudjom Djomani et al, 1999;Ojeda and Whitman, 2002;Stephen et al, 2003;Stark et al, 2003]. Authors using mirroring with Fourier-based coherence methods, such as periodogram, maximum entropy and multitaper methods, have reported that the recovered T e is usually overestimated when mirroring is performed [e.g., Lowry and Smith, 1994;Ojeda and Whitman, 2002;Stephen et al, 2003].…”
Section: Effect Of Mirroringmentioning
confidence: 99%
See 4 more Smart Citations
“…[36] The preprocessing technique of mirroring the gravity/topography data before performing a Fourier transform has been performed in many studies [e.g., Zuber et al, 1989;Lowry and Smith, 1994;Macario et al, 1995;Hartley et al, 1996;McKenzie and Fairhead, 1997;Poudjom Djomani et al, 1999;Ojeda and Whitman, 2002;Stephen et al, 2003;Stark et al, 2003]. Authors using mirroring with Fourier-based coherence methods, such as periodogram, maximum entropy and multitaper methods, have reported that the recovered T e is usually overestimated when mirroring is performed [e.g., Lowry and Smith, 1994;Ojeda and Whitman, 2002;Stephen et al, 2003].…”
Section: Effect Of Mirroringmentioning
confidence: 99%
“…The initial load at the Moho causes a deflection of amplitude h B at the surface, resulting in a new Moho topography of w B . Here we use the sign convention used by Forsyth [1985], though not by Stark et al [2003], that all deflections away from the center of the Earth are positive, whether they occur at the surface or at the Moho. Therefore, the final surface topography after flexure is:…”
Section: Appendix A: Plate Flexure Equationmentioning
confidence: 99%
See 3 more Smart Citations